PERAN KEPEMIMPINAN PENDIDIKAN ISLAM DALAM MANAJEMEN PERUBAHAN ORGANISASI PENDIDIKAN - Rachmad Sobri (Pascasarjana IAIN Sorong, 2019)
This article discusses changes in Islamic education organizations, who raised the role of Islamic education leadership in the change management of mini research education organizations at MTs Al-Mujahirin Patuk Yogyakarta. Basically every organization will make changes in the body of the organization is logical and formal. Good organizational change is a systemic and planned change and requires a top leader to drive a change and be suported by elements within it.